2007
DOI: 10.1002/asi.20756
|View full text |Cite
|
Sign up to set email alerts
|

A tool for data cube construction from structurally heterogeneous XML documents

Abstract: In neonates and infants with critical aortic coarctation, balloon angioplasty is considered for rescue therapy of heart failure. The use of conventional stents is limited because of further vessel growth, the need of redilation, and later surgical removal. However, a novel bioabsorbable magnesium stent (AMS) might overcome such restrictions of vessel stenting in newborns. Presented is the first use of an AMS for acute treatment of a newborn with severely impaired heart function due to a long segment recoarctat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In [28], [35], and [36] it is shown that XQuery is not the most suitable query language for this purpose. This is because the effective use of path expressions necessitates fairly extensive advance knowledge of the structures and naming conventions in the underlying documents.…”
Section: Extraction Strategies For Xml Datamentioning
confidence: 99%
“…In [28], [35], and [36] it is shown that XQuery is not the most suitable query language for this purpose. This is because the effective use of path expressions necessitates fairly extensive advance knowledge of the structures and naming conventions in the underlying documents.…”
Section: Extraction Strategies For Xml Datamentioning
confidence: 99%
“…In particular they propose SLCA [41] and MLCA [25] whose general intuition is that the LCA must be minimal. However, in [28,32] they showed that these approaches still produced undesired combinations between data items in some cases (e.g. when a data item needs to be combined with a data item at a lower level of the document hierarchy).…”
Section: Related Workmentioning
confidence: 99%
“…This is due to the fact that the element product-set (row 2) is the ancestor for the two product elements (in rows 7 and 13) that have sub-elements whose labels match to the searched keywords and thus, based on the rule (2), the element product-set is excluded from the query result. Näppilä et al (2008) introduced the SPC semantics as an answer to the problems related to SLCA and MLCA semantics. Since it is problematic for these kinds of data extraction strategies to return the best LCA nodes or sub-trees rooted by them, the SPC semantics instead returns only the exact data related to the nodes corresponding to the searched keywords.…”
Section: Xml Data Extractionmentioning
confidence: 99%